Pengembangan Pop-Up Book Digital untuk Meningkatkan Pemahaman Siswa pada Materi Kegiatan Ekonomi Kelas IV SD - Rizky Rindayu Maulifia; Nurdinah Hanifah; Aah Ahmad Syahid (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
This research is motivated by students who tend to be easily bored in learning and ignore the material being taught. This happens because the teacher's ability to use learning media is fairly less qualified. Teachers mostly use conventional learning media and do not utilize digital developments. Thus, the purpose of this research is to analyze the needs, design, develop digital learning media, especially Digital Pop-up Book by conducting feasibility tests evaluated by experts, increasing student understanding, and obtaining feedback from users. The research method used is Research and Development (R&D) by applying the ADDIE procedure which has five stages, namely analysis, design, development, implementation, and evaluation. Based on the study's results, the evaluation of media feasibility was carried out by three experts, namely material experts gave a score of 94%, media experts gave a score of 94% and practitioner experts gave a score of 93%. This product trial was conducted at SDN Periuk 1 Tangerang by conducting three meetings, namely pretest, treatment, and posttest. Based on the results of the comprehension test, shows an increase in student understanding by using Pop-up Book Digital media in learning. Pop-up Book Digital media received positive responses from students, namely by obtaining a score of 86.4% with a very good category through a student response questionnaire sheet.